ADAPTASI PRANATA KELUARGA PADA PROSES PEMBELAJARAN E-LEARNING DALAM MENGHADAPI DAMPAK PANDEMI COVID-19 - Devi, Nourma Ulva Kumala (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2020)
Family has an important role in shaping culture and healthy behavior. The first environment for children and other family members to socialize and learn about clean and healthy living norms is the family environment. From the start of the individual family education, a good community order can be created and a culture and healthy behavior can be instilled earlier. In addition, the family is a place to gather, discuss, share and socialize for all family members. In accordance with the function of the family as a place to socialize and learn, the family acts as an institution capable of providing education and as an "agent of change" to adapt to the impact of the Covid-19 pandemic, especially for children at the primary school level. Family support is very important in dealing with the COVID-19 pandemic crisis. In line with that, online learning systems also need to adapt to emphasize more on the role of the family (family centered). This is where parental assistance is needed so that children have self-regulating so that they are able to teach children in an effort to provide internal reinforcement that online learning forms independence. Keywords: Family , Covid-19, Self-Regulating, Online Learning (online)